If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + 4 + 4v + -2v + 6 = 11 Reorder the terms: 9 + 4 + 6 + 4v + -2v = 11 Combine like terms: 9 + 4 = 13 13 + 6 + 4v + -2v = 11 Combine like terms: 13 + 6 = 19 19 + 4v + -2v = 11 Combine like terms: 4v + -2v = 2v 19 + 2v = 11 Solving 19 + 2v = 11 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-19' to each side of the equation. 19 + -19 + 2v = 11 + -19 Combine like terms: 19 + -19 = 0 0 + 2v = 11 + -19 2v = 11 + -19 Combine like terms: 11 + -19 = -8 2v = -8 Divide each side by '2'. v = -4 Simplifying v = -4
| 15.6=2x-1.2 | | 80-2(p+1)=-20+48p | | .006x^3=6572 | | 3-2(2)-5=5(2)-22+3(2) | | 144=4q+4q | | 4x-3=3(-1+x) | | x+6forx=13 | | 120=p+7p | | 2x-3=-4+x | | 3x+(4x-1)=90 | | 0.1t=.4+.3t | | 8m+m=90 | | X+2x-1=2(-1+x) | | (4x^2-9x-9)= | | -x^2+515x-7500=0 | | 10x-45=3(b-15) | | h(t)=196-16t^2 | | x^2+515x-7500=0 | | -3n+3(5n-4)=8n-2(-8n+6) | | 6n+2n=96 | | 5x-(8x+4)=8x+-15 | | 2z+9z=4z+45+22 | | 5x(8x+4)=8x-15 | | -2(8r+2)-5(1-2r)=-r-3-4r | | 2n+2u=p | | 5(2+2x)=9(x-3) | | -2-5=7n | | 27-u=172 | | 6-2n=4n+4 | | (5x^2-11x+4)= | | x^2+545x-7500=0 | | -3(2-5m)=2(7m-5) |